Outcomes of endoscopic retrograde cholangiopancreatography in patients with situs inversus viscerum - Long Le; Nicholas McDonald; Anders Westanmo; Mohammad Bilal; Dharma Sunjaya (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims Situs inversus viscerum (SIV) is a congenital condition defined by left-to-right transposition of all visceral organs. This anatomical variant has caused technical challenges in endoscopic retrograde cholangiopancreatography (ERCP). Data on ERCP in patients with SIV are limited to case reports of unknown clinical and technical success rates. This study aimed to evaluate the clinical and technical success rates of ERCP in patients with SIV. Methods Data from patients with SIV who underwent ERCP were retrospectively reviewed. The data were collected by querying the nationwide Veterans Affairs Health System database for patients diagnosed with SIV who underwent ERCP. Patient demographics and procedural characteristics were collected. Results Eight patients with SIV who underwent ERCP were included. Choledocholithiasis was the most common indication for ERCP (62.5%). The technical success rate was 63%. Subsequent ERCP with interventional radiology-assisted rendezvous has increased the technical success rate to 100%. Clinical success was achieved in 63% of cases. Among cases of subsequent rendezvous ERCP after conventional ERCP failure, clinical success was achieved in 100%. Conclusions The clinical and technical success rates of ERCP in patients with SIV were both 63%. In patients with SIV in whom ERCP fails, interventional radiology-assisted rendezvous ERCP can be considered.